Muzikos terapijos profesinio pripažinimo Europos Sąjungoje apžvalga - Letulė, Nerdinga; Ala-Ruona, Esa (Special Education, 2016)
This article documents the development of the professional recognition of music therapy in the EU. First, a brief history of the origins of modern music therapy in Europe is presented, followed by more detailed analysis of the establishment of training courses and professional associations across Europe. Second, the stages in the professionalization process according to Ridder, Lerner and Suvini (2015) are discussed. Third, the importance of the European Music Therapy Confederation in promoting music therapy recognition in the EU is highlighted.